Normal delivery or cesarian? An avaliation from the client’s perception - Leila Memória Paiva Moraes; Maria Vera Lúcia Moreira Leitão Cardoso; Mônica Oliveira Batista Oriá; Isolda Pereira da Silveira (Rev Rene)
We have done an exploratory, descriptive study with parturients, except those which were in expulsive period. We intented woman aware of the fact that normal delivery is safer to their babies and to themselves, however emotional aspects including fear and pain had influenced all process resolution, thus the nurse assistance, prenatal care and attendance during all stages of labor and puerperian have been indispensable, giving more humane attention to its clients.